Assessment of the physical and mechanical properties of Pseudocedrela kotschyi wood from Ghana's savannah zone - Wongara Ibrahim, Bashiru (Acta silvae et ligni, 2026)
This study assessed the physical and mechanical properties of Pseudocedrela kotschyi wood from Ghana's Savannah zone using three mature trees from Jeyiri in the Wa East District. Specimens from the bottom, middle, and top stem sections were tested following BS 373 (1957) protocols. The results revealed significant vertical gradients in wood properties: moisture content increased with height from 44.5% to 49.54% (p = 0.001), while density also decreased from 747.92 kg/m3 to 705.63 kg/m3 (p = 0.042). Dimensional stability deteriorated upward, with volumetric shrinkage rising from 9.48% to 12.46% (p = 0.005) and volumetric swelling increasing from 10.09% to 15.41% (p = 0.003). All mechanical properties declined with height: the modulus of elasticity decreased from 4,801 to 4,077 MPa, the modulus of rupture from 24.26 to 19.95 MPa, compression strength from 37.82 to 33.96 MPa, and shear strength from 16.62 to 13.08 MPa. Overall, P. kotschyi exhibits medium-density hardwood characteristics and requires position-based utilization and grading strategies.
Keywords: dimensional stability; dimenzijska stabilnost; izraba lesa; lastnosti lesa; mechanical properties; mehanske lastnosti; območje savane; position-based grading; Pseudocedrela kotschyi; razvrščanje na podlagi položaja; savannah zone; timber utilization; tropical hardwood; tropski trdi les; vertical variation; vertikalne variacije; wood properties